Adsorption Thermodynamic Study of Congo Red Dye on Electrospun Nanofibers Mat of Polyacrylonitrile - Juman A. Naser (Journal of Global Pharma Technology, 2016)
The present study intends to prepare nanofibers mat of polyacrylonitrile by electrospinning technique and investigates their adsorption capacity to Congo red dye from the aqueous solution, after characterize it by different techniques such as FTIR, SEM, EDA, XRD and BET. The influence factors on adsorption were studied including adsorbent dosage, initial concentration, contact time, pH and ionic strength. The results confirmed that the increasing in pH decreases the adsorption capacity. So, the optimum adsorbent dosage, initial concentration and contact time were 0.006 g, 25 mg/L and 150 min respectively. The isotherm models of Freundlich and Langmuir were applied on the experimental adsorption data to evaluate the maximum capacity and energy of adsorption. The experimental data was founded more fitted with Langmuir model. Additional, the thermodynamic parameter changes such ∆G, ∆H and ∆S of adsorption were estimated. The results explained that the adsorption process was exothermic and non-spontaneous.Keywords: Electrospinning, Congo red dye, Polyacrylonitrile, Nanofiber, Adsorption.